Differential expression and regulation of the glucokinase gene in liver and islets of Langerhans. - Iynedjian, P B (1989)
Glucokinase, a key regulatory enzyme of glucose metabolism in mammals, provides an interesting model of tissue-specific gene expression. The single-copy gene is expressed principally in liver, where it gives rise to a 2.4-kilobase mRNA. The islets of Langerhans of the pancreas also contain glucokinase. Using a cDNA complementary to rat liver glucokinase mRNA, we show that normal pancreatic islets and tumoral islet cells contain a glucokinase mRNA species approximately 400 nucleotides longer than hepatic mRNA. Hybridization with synthetic oligonucleotides and primer-extension analysis show that the liver and islet glucokinase mRNAs differ in the 5' region. Glucokinase mRNA is absent from the livers of fasted rats and is strongly induced within hours by an oral glucose load. In contrast, islet glucokinase mRNA is expressed at a constant level during the fasting-refeeding cycle. The level of glucokinase protein in islets measured by immunoblotting is unaffected by fasting and refeeding, whereas a 3-fold increase in the amount of enzyme occurs in liver during the transition from fasting to refeeding. From these data, we conclude (i) that alternative splicing and/or the use of distinct tissue-specific promoters generate structurally distinct mRNA species in liver and islets of Langerhans and (ii) that tissue-specific transcription mechanisms result in inducible expression of the glucokinase gene in liver but not in islets during the fasting-refeeding transition.